Is the sport an illusory wellfare on the subject? - R. Rodrigues (Desafio Singular, 2008)
We start from the theory of that the "welfare" of the subject in the sport is analyzed by the area of the Physical Education as what promotes the condition of physical health and provides the emotional equilibrium. This analysis is centered on the premise that in the field of the biological and psychological sciences, the sporting practices provides beneficial results to the individual, that is, "sport is health". However, of the reading of the Freud text titled the "Civilization and Its Discontents" we are going to analyze other relations that the subjects can establish with the sport. In that case, we understand the sport for the subject, considering two approaches, that is, as a substituting approach or sublimation for the man to find the satisfaction of his "impulses". We put in doubt would be been possible the achievement of a sporting practice that permitted to the subject a objetal relation in which he can find to full satisfaction of his "impulses".